Fantasy Gymnastics Learning Video Based on Fable Stories to Stimulate the Imagination of Early Childhood - Putu Gita Cintya Dewi; Putu Aditya Antara; Made Vina Arie Paramita (Universitas Pendidikan Ganesha, 2024)
Lack of media or supporting facilities for learning in schools results in delays in children's cognitive development, such as the child's imagination process. Based on this, a study aimed to analyze the Fantasy Gymnastics Learning Video Based on Fable Stories to Stimulate the Imagination of Early Childhood Group B Kindergarten. The subjects in this study were 20 children in group B, with the object of research being the imagination ability of early childhood. The research model used was the ADDIE model. The data collection method used was a questionnaire and observation. The instrument used was a questionnaire sheet. The data analysis technique used was quantitative and qualitative analysis. The results of the feasibility and practicality test of the media obtained very decent results from experts and practitioners. The effectiveness test results showed that H1 was accepted and H0 was rejected, so it can be concluded that the fantasy gymnastics learning video based on fable stories is declared effective in stimulating the development of early childhood imagination. This study implies that the fantasy gymnastics learning video based on fable stories can facilitate students' learning and help teachers achieve more optimal learning goals.